The Impact Of Money Supply, Interest Rates, And Exchange Rates On Inflation In Indonesia - Maharani Intan Syafira; Andini Septiani; Gina Septiana (CAKRAWALA : Management Science Journal, 2024)
The purpose of this study is to collect empirical data on the relative and simultaneous effects of money supply, interest rates, and exchange rates on inflation in Indonesia. The websites www.bps.go.id and www.bi.go.id, which provide access to Bank Indonesia, provide the data used in this study. Data on Indonesia's money supply, interest rates, and exchange rates for 2019-2023 were also used, along with data on Indonesia's inflation rate. The data collection methods used were observation and literature study. Multiple Linear Regression Analysis is the data analysis approach used in this study, which utilizes descriptive statistics with the IBM SPPS Statistics 25 tool. The findings of this study indicate that there is no positive significant effect on inflation caused by money supply and a positive significant effect of interest rates and currency exchange rates on Indonesian inflation. These findings can be used as a consideration in monetary policy in Indonesia. The government and Bank Indonesia should consider interest rates and exchange rates when formulating monetary policy to balance inflation and economic growth.